Coexistence and different determinants of posttraumatic stress disorder and posttraumatic growth among Chinese survivors after earthquake: role of resilience and rumination - Wu, Kaijun; Zhang, Yuqing; Liu, Zhengkui; Zhou, Peiling; Wei, Chuguang (Frontiers in Psychology, 2015)
Posttraumatic stress disorder (PTSD) and posttraumatic growth (PTG) are two different outcomes that may occur after experiencing traumatic events. Resilience and rumination are two important factors that determine the development of these outcomes after trauma. We investigated the association between these two factors, PTSD and PTG, among Chinese survivors in an earthquake. With a convenience sample of 318 survivors from earthquake, we measured trauma exposure, PTSD, PTG, resilience, and rumination (IES-R, PTGI, 10 item CD-RISC, RRS). Then we used bivariate correlation and structural equation modeling to examine the structure of relations among these factors. Results showed that resilience and reflective rumination have a positive effect on PTG (β = 0.32, p < 0.001; β = 0.17, p = 0.049). Earthquake exposure, brooding rumination and depressed-related rumination are related with higher level of PTSD (β = 0.10, p = 0.021; β = 0.33, p < 0.001; β = 0.36, p < 0.001). The findings suggest distinct determinants of the negative and positive outcomes, and this may provide better understanding about the risk and protective factors for traumatic reactions.